2018
DOI: 10.1074/jbc.ra118.003648
|View full text |Cite
|
Sign up to set email alerts
|

Structural mapping of fluorescently-tagged, functional nhTMEM16 scramblase in a lipid bilayer

Abstract: Most members of the TransMEMbrane protein 16 (TMEM16) family are Ca-regulated scramblases that facilitate the bidirectional movement of phospholipids across membranes necessary for diverse physiological processes. The nhTMEM16 scramblase (from the fungus ) is a homodimer with a large cytoplasmic region and a hydrophilic, membrane-exposed groove in each monomer. The groove provides the transbilayer conduit for lipids, but the mechanism by which Ca regulates it is not clear. Because fusion of large protein tags … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…1b), making them an obvious choice for fluorescence microscopy applications 30 . We recently showed that ATTO488 can be rendered non-fluorescent by chemical reduction with the membrane-impermeant dianion dithionite 31 , suggesting that ATTO488-modified phospholipids could be suitable reporters of scramblase activity in microscopy-based assays. We tested this possibility in a cuvette-based assay as follows: Proteoliposomes were reconstituted using egg phosphatidylcholine, trace amounts of ATTO488-PE and biotinylated phosphatidylethanolamine (biotin-PE), and Triton X-100-solubilized yeast ER membrane proteins ('Triton Extract' or TE), as described previously 9,11 .…”
Section: Atto488-phosphatidylethanolamine (Atto488-pementioning
confidence: 99%
“…1b), making them an obvious choice for fluorescence microscopy applications 30 . We recently showed that ATTO488 can be rendered non-fluorescent by chemical reduction with the membrane-impermeant dianion dithionite 31 , suggesting that ATTO488-modified phospholipids could be suitable reporters of scramblase activity in microscopy-based assays. We tested this possibility in a cuvette-based assay as follows: Proteoliposomes were reconstituted using egg phosphatidylcholine, trace amounts of ATTO488-PE and biotinylated phosphatidylethanolamine (biotin-PE), and Triton X-100-solubilized yeast ER membrane proteins ('Triton Extract' or TE), as described previously 9,11 .…”
Section: Atto488-phosphatidylethanolamine (Atto488-pementioning
confidence: 99%
“…ANO5/TMEM16E/GDD1 (henceforth ANO5) belongs to the ten-member human Anoctamin/TMEM16 membrane protein family that includes Ca 2+ -activated ion channels (ANO1/TMEM16A, ANO2/TMEM16B) and phospholipid scramblases (ANO3, ANO4, ANO6, ANO7, and ANO10) 6,7 . In reconstitution-based assays ANO6/TMEM16F and its fungal homologues Aspergillus fumigatus TMEM16 (afTMEM16) and Nectria haematococca TMEM16 (nhTMEM16) show both scramblase and relatively unselective ion channel activity that are regulated by Ca 2+ 8–16 .…”
Section: Introductionmentioning
confidence: 99%
“…1 b), making them an obvious choice for fluorescence microscopy applications 35 . We recently showed that ATTO488 can be rendered non-fluorescent by chemical reduction with the membrane-impermeant dianion dithionite 36 , suggesting that ATTO488-modified phospholipids could be suitable reporters of scramblase activity in microscopy-based assays. We tested this possibility in a cuvette-based assay as follows.…”
Section: Resultsmentioning
confidence: 99%